COMORBIDITIES AS PREDICTORS OF CARDIOVASCULAR RISK AND SURVIVAL IN HYPERTENSIVE VERY ELDERLY PATIENTS. (June 2018) - Staiculescu, R.; Fronea, M.; Unugureanu, C.; Dediu, G.; Olteanu, D.; Balaceanu, B.; Gurau, D.; Balaceanu, A.
Abstract : Objective: The aim of the study was to assess the cardiovascular risk in hospitalised very elderly patients with multiple comorbidities. Design and method: The retrospective study included 82 patients admitted to Clinical Emergency Hospital between January 2014-May 2017. Results: Patients in the study group were aged between 90 and 98 years, with an average age of 95 years. Gender distribution: 67% female and 33% male. 87.8% were presented to Acute Medical Unit. 63.4% of patients were already diagnosed with hypertension. Depending on severity the following distribution was observed: grade I 9.6%, grade II 63.4%, grade III 25%. One patient had secundary hypertension asociated with renal parenchymal disease. Comorbidities in hypertensive patients: chronic kidney disease evaluated by MDRD equation was encountered in 98% of cases, with the following staging: G2 28.8%, G3a 32.6%, G3b 24%, G4 9.6% and G5 28.8%. As electrolytes imbalance we noticed: hyponatremia in 15.3% of cases, hypernatremia in 3.8%, hypokalemia in 32.6% and hyperkalemia in 3.8%. Only 3.8% of patients had hypercholesterolaemia. 23% were diagnosed with diabetes mellitus and had established treatment. Regarding the state of nutrition, 25% were cachectic patients and 17.3 were obese, and bedsores were found in 21% of them. Transthoracic echocardiography was performed in 26 patients. It showed heart valve calcifications in 73% of cases, diastolic dysfunction in 23% of cases and left ventricle hypertrophy in 46.15% of cases. 69% of the hypertensive patiens studied had systemic atherosclerosis and 21% had stroke sequels. Hyperuricemia was also found in 23% of cases. 42% of patients had impaired cognitive performance, including dementia. For all the patients the average time spent in hospital was 6 days, with a maximum of 12 days. Conclusions: The majority of the elderly patients with hypertension had multiple comorbidities. Chronic kidney disease was the most common comorbidity found, systemic atherosclerosis and impaired cognitive performance are very frequent in these patients. Comorbidities are the most important predictors of cardiovascular disease risk and mortality in very elderly patients.